STEIN - Stochastic erosion in-situ cosmogenic nuclide model - Dennis, Donovan P.; Scherler, Dirk (GFZ Data Services, 2022)
Abstract The stochastic erosion in-situ cosmogenic nuclide model is a 1D numerical model that simulates the evolution of the concentrations of in situ-produced Be-10, C-14, and He-3 alongside the bedrock thermal field in the shallow Earth surface. It is useful for evaluating cosmogenic nuclide data derived from field samples, in order to determine the erosion rate, erosion style, as well as the time-integrated bedrock thermal history. The model simulates erosion in four styles: no erosion, uniform (steady-state) erosion, episodic erosion, and stochastic erosion. It is particularly useful for evaluating the time-temperature evolution of bedrock hillslopes in mountainous regions. TechnicalInfo Copyright 2022 Helmholtz Centre Potsdam GFZ German Research Centre for Geosciences Redistribution and use in source and binary forms, with or without modification, are permitted provided that the following conditions are met: - Redistributions of source code must retain the above copyright notice, this list of conditions and the following disclaimer. - Redistributions in binary form must reproduce the above copyright notice, this list of conditions and the following disclaimer in the documentation and/or other materials provided with the distribution. - Neither the name of the copyright holder nor the names of its contributors may be used to endorse or promote products derived from this software without specific prior written permission. THIS SOFTWARE IS PROVIDED BY THE COPYRIGHT HOLDERS AND CONTRIBUTORS "AS IS" AND ANY EXPRESS OR IMPLIED WARRANTIES, INCLUDING, BUT NOT LIMITED TO, THE IMPLIED WARRANTIES OF MERCHANTABILITY AND FITNESS FOR A PARTICULAR PURPOSE ARE DISCLAIMED. IN NO EVENT SHALL THE COPYRIGHT HOLDER OR CONTRIBUTORS BE LIABLE FOR ANY DIRECT, INDIRECT, INCIDENTAL, SPECIAL, EXEMPLARY, OR CONSEQUENTIAL DAMAGES (INCLUDING, BUT NOT LIMITED TO, PROCUREMENT OF SUBSTITUTE GOODS OR SERVICES; LOSS OF USE, DATA, OR PROFITS; OR BUSINESS INTERRUPTION) HOWEVER CAUSED AND ON ANY THEORY OF LIABILITY, WHETHER IN CONTRACT, STRICT LIABILITY, OR TORT (INCLUDING NEGLIGENCE OR OTHERWISE) ARISING IN ANY WAY OUT OF THE USE OF THIS SOFTWARE, EVEN IF ADVISED OF THE POSSIBILITY OF SUCH DAMAGE.